GAMBARAN INTENSITAS NYERI DAN MANAJEMEN DISMENORE PADA REMAJA PUTRI DI SMAN 1 MODEL TAMBANG - Asbullah Asbullah; Darwin Karim; Erika Erika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Dysmenorrhea is characterized by lower abdominal pain, with  the level of pain vary ranging from mild to severe and management of dysmenorrhea can be used with several ways such as pharmacological, non-pharmacological and mixed. The purpose of this research is representation intensity of pain and management dysmenorrhea in teenager of Tambang Senior High School, Through quantitative research and descriptive design. In this research the population is a randomly selected teenage girl of Tambang Senior High School the sample 168 respondent are taken based on inclusion criteria. The instrument in this research used is numerical rating scale for the variable of pain level and the questionnaire fot the variable of management dysmenorrhea. The result of this research  findings characteristic of respondents aged 17 (32,1%) and menarche most when i was of respondents aged 12 (31,5%). Most respondent experience dysmenorrhea with moderate pain respondents 79 (47,0%). Majority management of dysmenorrhea with non-pharmacological respondent 88 (52,4%). The majority of the respondents were feminax drug therapists hen 55 (32,7%). The majority of non-pharmacological management is done by respondents with a rest of 133 (79.2%). Research this study suggests that adolescents who experience dysmenorrhea to make proper management, so that the pain does not interfere with learning activities at school.  Keywords: dysmenorrhea, female students, management dysmenorrhea